2020
DOI: 10.1016/j.rmcr.2020.101205
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in severe COVID-19 infection: A case series

Abstract: Evidence supporting the use of dexamethasone in severe COVID-19 patients is emerging. In this case series, we share our experience in using dexamethasone in five COVID-19 infected patients with acute respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Expectedly, high-dose, short-term corticosteroid therapy in early respiratory distress has been associated with better prognosis [118]. Several clinical reports have demonstrated that the use of corticosteroids in severe COVID-19 provides multiple clinical benefits, including reductions in the need for and duration of invasive ventilation [119][120][121][122].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Expectedly, high-dose, short-term corticosteroid therapy in early respiratory distress has been associated with better prognosis [118]. Several clinical reports have demonstrated that the use of corticosteroids in severe COVID-19 provides multiple clinical benefits, including reductions in the need for and duration of invasive ventilation [119][120][121][122].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Dexamethasone treatment in CoVID-19 patients who were receiving mechanical ventilation support results in lower mortality rate 123 . Severe CoVID-19 cases have been brought to remission state after 6 mg once a day intravenous administration of dexamethasone 124 .…”
Section: Is Butyrate An Alternative To Dexamethasone?mentioning
confidence: 99%
“…Dexamethasone is indicated as a therapeutic option for immune thrombocytopenic purpura associated with CoVID-19 124 , 125 . Administration of dexamethasone before 30 hours of ARDS onset can significantly reduce the period of mechanical ventilation and mortality 12 .…”
Section: Is Butyrate An Alternative To Dexamethasone?mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are no exact specific antiviral treatments or vaccines for the COVID-19 disease (M. Kumar et al, 2020a , 2020b ). Therefore, to treat or alleviate its symptoms, some drugs are being clinically evaluated, including chloroquine (CQ) and hydroxychloroquine (HCQ) ( Borba et al, 2020 ; Gao et al, 2020 ; Magagnoli et al, 2020 ; Tang et al, 2020 ), azithromycin (AZT) ( Arshad et al, 2020 ; Dubernet et al, 2020 ), ivermectin (IVM) ( Caly et al, 2020 ; Yang et al, 2020 ), dexamethasone (DEX) ( Hassan et al, 2020 ; Johnson and Vinetz, 2020 ; Lester et al, 2020 ; Selvaraj, 2020 ) and some HIV antivirals ( Agrawal et al, 2020 ; Alvi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%